Safety Assessment of Cooperative Platooning in Mixed Traffic † - Park, B. Brian; Lee, Hyejin; Yun, Ilsoo; Park, Jeehyung (Engineering Proceedings, 2023)
The safety impacts of cooperative platooning in mixed traffic consisting of human-driven, connected, and connected–automated vehicles were evaluated. The cooperative platooning, in the case of the mixed traffic control algorithm evaluated here, was cooperative adaptive cruise control with an unconnected vehicle (CACCu). Its safety and string stability were evaluated using a high-fidelity simulation based on real-world vehicle trajectories. An adaptive cruise control (ACC) algorithm was selected for comparison purposes. The results indicate that the cooperative platooning in mixed traffic control algorithm (CACCu) maintains string stability and operates with greater safety than the ACC.
Keywords: cooperative adaptive cruise control; cooperative platooning; NGSIM; safety assessment; surrogate safety